EVALUASI DATA ESTIMASI CURAH HUJAN SATELIT TRMM 3B42 DENGAN DATA OBSERVASI DI KOLAKA TAHUN 2019 - Satria WD, Hendri; Qothrunada, Dewi Tamara (EduFisika: Jurnal Pendidikan Fisika, 2022)
Precipitation data in Indonesia is currently carried out by in situ observation, which allows for blank data due to observer errors or due to damaged equipment. The TRMM satellite is one of the satellites that is widely used to fill in the blank rainfall data in Indonesia. This study aims to determine the results of the accuracy between the TRMM 3B42 satellite rainfall estimation data and surface observation data sourced from the Sangia Ni Bandera Kolaka Meteorological Station in 2019. Both data were statistically tested using the correlation coefficient calculation method, error calculation using the Root Mean method Squared Error (RMSE), and significance test. The results showed that the best relationship was produced by dry months compared to wet months. In general, in the time series graph, the satellite data and observation data show a fairly similar fluctuation pattern, but in some cases the TRMM satellite data is much smaller than the observation data. The best time scale for the relationship between the two data is the basic time scale, because it produces significant results for all periods of the month, and has a high correlation value with a small error value.